Finite element analysis of heat sink in term of thermal and temperature distribution with different chip power input - Mohamed, Mazlan; Nazri Omar, Mohd; Shaiful Ashrul Ishak, Mohamad; Rahman, Rozyanty; Fahmi Mohd Roslan, Muhamad; Nur Hafiz Shaidan, Muhammad; Ismael Rizman, Zairi (International Journal of Engineering and Technology, 2018)
This paper presents the simulation of heat sink by using Workbench 18.0 Software to simulate the temperature distribution at different chip power input. 3D model of heat sink is generated using Design Modeler using the same dimension with experimental setup. The study was made for a heat sink mounted on the power source (Chip) under different types of chip powers. The results are presented in terms of temperature distribution when chip powers have been increased from 1 W to 10 W. The temperature distribution is been observed and it was found that the temperature distribution of the heat sink has lower temperature when power source at 1 W and increase significantly when the power source rise up to 10 W. The increase the temperature of heat sink is from 30.8ÂºC up to 96.2ÂºC estimated to be 212% the increase of temperature. The simulation also been verify by using different time step use during the simulation and using grid independency test to ensure the simulation result is accurate.Â